Analysis of Duty Cycle, Inductance, and Capacitance Variations on Buck Converter Performance Using PSIM Software - Isra' Nuur Darmawan; Kholistianingsih Kholistianingsih; Slamet Fajar Budhi Nugroho; Nur Johara (Applied Engineering, Innovation, and Technology, 2025)
This study investigates the influence of duty cycle, inductance, and capacitance variations on the performance of a buck converter through simulation using PSIM software. The research aims to quantify how these parameters affect output voltage and ripple, which are key factors in achieving efficient and stable DC–DC conversion for renewable energy applications. The converter was modeled with an input voltage of 48 V, an intended output voltage of 24 V, and a switching frequency of 20 kHz. Simulation results show that the output voltage increases linearly with the duty cycle. At a 50% duty cycle, the converter achieved an output voltage of 23.9 V, confirming accurate voltage regulation. Furthermore, ripple voltage was found to decrease significantly with higher inductance and capacitance values, reaching a minimum of 0.1 V when L is 750 μH and C is 1,250 μF. These results demonstrate that optimizing LC parameters can substantially improve voltage stability and filtering efficiency. The findings provide practical design guidance for high-efficiency buck converters used in renewable energy and power electronic applications.